Shot mechanical analysis according to shooting performance in youth basketball players - Fatih Kılınç; Ömer Pamuk (Turkish Journal of Kinesiology)
In basketball, shooting stands out as a vital technique directly affecting the game results. Identifying shooting mechanics early in a basketball player's career can significantly develop shooting performance in subsequent years. This study aimed to explore shooting percentages based on angular positions of joint parts in the shooting techniques of youth basketball players. Fifteen male participants (average age: 14.1±0.7 years, height: 180.7±7.9 cm, body weight: 65.4±10.0 kg, sports experience: 4.7±0.4 years) voluntarily participated in the study. They were divided into high shooting rate (n: 7) and low shooting rate (n: 8) groups. Both groups attempted 60 shots from the free throw line (20 shots), right forward position (20 shots), and left forward position (20 shots). Joint angle values during the initial and final shooting phases were compared between groups using Independent t-tests. Significant differences were found between groups in the shoulder part during the beginning phase and the wrist part during the final shooting phase (p